FORMATION OF THE SUBJECT OF INTERCULTURAL COMMUNICATION IN FOREIGN-LANGUAGE EDUCATION (Journal of Educational Sciences, 2018)
The article deals with the formation of the language personality, which is characteristic of language education. The language education in Kazakhstan includes teaching Kazakh and Russian languages,respectively; the language personality is formed at study of these languages. When studying a foreign language, a subject of intercultural communication is formed. In this regard, the linguistic personalityhas two of the above-named species, depending on what is the object of study language or foreign language education. A student in foreign-language education uses cognitive strategies of his culture as basiccognitive images, he uses them in cognition of the new culture of the country of the studied language. As a subject of intercultural communication, such a student is guided by new knowledge about his ownculture discovered in the process of cognition of his own culture. In the paper the main trends in teaching a foreign language are formulated. In particular, the revision of strategic directions for teaching a foreign language leads to a revision of the methodological training of a foreign language teacher and requires a teacher of a new education; the methodological basis for teaching a foreign language is the cognitive-linguistic culture methodology; the object of study «lingvaculture » synthesizes «language-culture-personality» and reflects the goal of forming «subject of intercultural communication» as an integral subject of scientific researches; intercultural and communicative competence has become the object of the formation of a foreign language.Key words: language education, foreign language education, subject of intercultural communication,language personality.